Data Mining: An Approach of Prediction of Manpower Placement: Utilizing Data Mining for Predictive Manpower Placement in Engineering (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The data utilized as a part of this work was the data provided by the Kochi nodal focal point of National Technical Manpower Data System (NTMIS). Data is arranged by the nodal focus from the input given by graduates, post graduates, and recognition holders in designing from different building universities and polytechnics situated inside the state. This overview of specialized labor data was initially done by the Board of Apprenticeship Training (BOAT) for different individual foundations.